Ocular cysticercosis: an epidemiological study - Ehrenfried O. Wittig (Arquivos de Neuro-Psiquiatria)
The objetive of the research was to verify the incidence of the ocular form of cysticercosis among the patients who consulted professionals of the field, during the first statistic inventory accomplished in the State of Paraná, Brazil. The 1996 research was performed through a questionnaire sent to all 220 members of Paraná Ophthalmology Association and to the 17 members of Pathology and Cytology Department of the Paraná Medical Association. A pre-stamped envelop for the return of the answers was included in the package. We received 99 answers from ophthalmologists and 10 answers from pathologists. Retrospective and epidemiological research about the incidences of the ocular cysticercosis in the State of Paraná, added to national related published reports, rendered 95 cases probably adquired in Paraná, 71 of the cases were referred in this research and 24 in prior publication. The most frequent localization was vitreous and subretinal, as literature had already pointed out.